2021
DOI: 10.1186/s40478-021-01152-3
|View full text |Cite
|
Sign up to set email alerts
|

Space-occupying brain lesions, trauma-related tau astrogliopathy, and ARTAG: a report of two cases and a literature review

Abstract: Astrocytes with intracellular accumulations of misfolded phosphorylated tau protein have been observed in advanced-stage chronic traumatic encephalopathy (CTE) and in other neurodegenerative conditions. There is a growing awareness that astrocytic tau inclusions are also relatively common in the brains of persons over 70 years of age—affecting approximately one-third of autopsied individuals. The pathologic hallmarks of aging-related tau astrogliopathy (ARTAG) include phosphorylated tau protein within thorn-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 82 publications
(136 reference statements)
0
10
0
Order By: Relevance
“…In Olmsted County, the incidence of PSP and CBS (corticobasal syndrome) increased over time, being 2.6 per 100,000 person-years and 0.4 per 100,000 person-years respectively [22], while another study found similar prevalence between them (around10.84/100,000) [23]. Most of patients are diagnosed at the age of 78 (70)(71)(72)(73)(74) for PSP, 75-79 for CBS [23]) with median survival time around 6 years [22].…”
Section: Epidemiology Of Tauopathiesmentioning
confidence: 97%
“…In Olmsted County, the incidence of PSP and CBS (corticobasal syndrome) increased over time, being 2.6 per 100,000 person-years and 0.4 per 100,000 person-years respectively [22], while another study found similar prevalence between them (around10.84/100,000) [23]. Most of patients are diagnosed at the age of 78 (70)(71)(72)(73)(74) for PSP, 75-79 for CBS [23]) with median survival time around 6 years [22].…”
Section: Epidemiology Of Tauopathiesmentioning
confidence: 97%
“…Recently, two patients with arachnoid cysts and a history of repetitive concussions were described to have extensive ARTAG and CTE‐pathology. The authors suggest that chronic mechanical stress could represent another trigger of astrocytic tau pathology [ 39 ]. In our study about one third of glioblastoma patients exhibited mild ARTAG, but the frequency and distribution did not differ from both control groups.…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been suggested that TSAs might be related to trauma while GFAs relate to neurodegeneration. Indeed, during a small case study of two individuals with large arachnoid cysts it was found that TSA pathology had resulted from long-term mechanical stress, and it is proposed that these inclusions may be different from neurodegenerative-associated ARTAG in the form of GFAs [ 89 ]. Further investigation in larger cohorts of cases of mechanical stress would be needed to answer this question.…”
Section: Artag In Other Astrocytic Tauopathiesmentioning
confidence: 99%
“…The results demonstrated that tau propagation in HEK cells required pairing of tau isoforms between the inoculum and the recipient substrate, meaning that propagation only occurs between cells expressing like-for-like tau [ 98 ]. Thus, there are currently two propagation hypotheses for ARTAG development, the first where neurons release tau which is taken up by nearby astrocytes and the second where astrocytes upregulate tau expression and kinases which lead to hyperphosphorylation and spread to other cells- see Figure 3 [ 89 ]. Whilst there is convincing support from cellular and animal models for the former hypothesis, this mode of propagation is not supported in disorders such as PiD where 4R ARTAG exists in association with 3R neuronal and astrocyte inclusions [ 78 ].…”
Section: Astrocytic Tau Propagationmentioning
confidence: 99%